2011
DOI: 10.1177/0883073810389043
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Duchenne Muscular Dystrophy: The Subjective Impact on Children and Parents

Abstract: Duchenne muscular dystrophy results in a broad spectrum of physical and psychosocial consequences, both to patient and caregivers. This study was aimed to explore health-related quality of life and its possible determinants in Duchenne muscular dystrophy children and in their parents. Caregivers (21 mothers and 6 fathers; mean age, 40.04 years) of 27 Duchenne muscular dystrophy patients (mean age, 11.26 years) completed the validated Children Health Questionnaire-Parent Form 50 and the Family Strain Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 24 publications
7
83
0
4
Order By: Relevance
“…Some studies have shown that it is reduced among children with DMD 6,7 . Others have found no differences between the QOL of children with DMD and healthy children 4,8,9 .…”
mentioning
confidence: 99%
“…Some studies have shown that it is reduced among children with DMD 6,7 . Others have found no differences between the QOL of children with DMD and healthy children 4,8,9 .…”
mentioning
confidence: 99%
“…The quality of life (QOL) of children with DMD is still controversial. Some studies have shown that it is reduced among children with DMD 6,7 . Others have found no differences between the QOL of children with DMD and healthy children 4,8,9 .…”
mentioning
confidence: 99%
“…10,11 Although physical and psychosocial domains of health-related quality of life are comparatively low in boys with DMD, psychosocial quality of life is sometimes higher in adolescents than in school-age children, indicating the development of coping strategies. [12][13][14] The psychosocial well-being of parents is greatly impacted, particularly around the time of a boy's transition to wheelchair use.…”
Section: Significance In Terms Of Ill Healthmentioning
confidence: 99%